2015
DOI: 10.1111/cpf.12296
|View full text |Cite
|
Sign up to set email alerts
|

A programme based on repeated hypoxia–hyperoxia exposure and light exercise enhances performance in athletes with overtraining syndrome: a pilot study

Abstract: Overtraining syndrome (OTS) is a major concern among endurance athletes and is a leading cause in preventing them to perform for long periods. Intermittent exposure to hypoxia has been shown to be an effective way of improving performance without exercising. Aim of this pilot study was to evaluate intermittent hypoxia-hyperoxia training combined with light exercise as an intervention to facilitate athletes with OTS to restore their usual performance level. Thirty-four track and field athletes were recruited: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 20 publications
2
29
0
5
Order By: Relevance
“…Exercise therapy is expected to improve skeletal muscle performance and maintain mobility in both humans and rodent models (Adams et al, 2008;Piazza et al, 2009). A recent study has shown that hypoxic exposure is an effective way to improve performance without exercising (Susta et al, 2017). Similarly, our study has shown that both exercise and NH could significantly improve the climbing ability of aged flies (Figure 5).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Exercise therapy is expected to improve skeletal muscle performance and maintain mobility in both humans and rodent models (Adams et al, 2008;Piazza et al, 2009). A recent study has shown that hypoxic exposure is an effective way to improve performance without exercising (Susta et al, 2017). Similarly, our study has shown that both exercise and NH could significantly improve the climbing ability of aged flies (Figure 5).…”
Section: Discussionsupporting
confidence: 70%
“…However, the effect of hypoxia combined with exercise remains unclear. Some studies have shown that intermittent moderate hypoxic exposure with low-intensity exercise can promote aerobic exercise ability (Casas et al, 2000) or intermittent hypoxia-hyperoxia training and low-intensity exercise can promote the functional recovery of overtraining syndrome in athletes (Susta et al, 2017), suggesting that hypoxia combined with lower-intensity exercise may produce better results (Jones and Grotewiel, 2011), which may also guide our future research investigations on hypoxia-exercise.…”
Section: Discussionmentioning
confidence: 93%
“…Exposure to normobaric intermittent hypoxia training (IHT) has been shown to improve exercise capacity without exercising in the elderly and in cardiac patients . IHT also positively affects autonomic nervous system functioning in various patients . This technique consists of intermittent exposures to hypoxic–normoxic stimuli (1 cycle of up to 5 hypoxic exposures lasting at least 5–6 minutes, followed by at least 5–6 minutes of normoxic air breathing) repeated almost daily (4–5 days a week) over 2 to 3 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…In our study we used normobaric intermittent hypoxic‐hyperoxic training (IHHT) as a new alternative treatment. Replacing normoxia with hyperoxia during intermittent exposure to hypoxia has been proven to be effective in preliminary studies focused on exercise performance . This new approach is more convenient than IHT, as the recovery time between bouts of exposure to hypoxia is shortened to 3 minutes, allowing for a higher number of hypoxia–hyperoxia cycles during the same session.…”
Section: Introductionmentioning
confidence: 99%
“…Susta et al [32] investigated sportsmen with overtraining syndrome with application a conditioning program consisting of repeated exposures to hypoxia (10% FiO 2 ) and hyperoxia (30% FiO 2 ) , 6-8 cycles (total time 45 min -1 h), three times a week, delivered 1·5-2 h after a low-intensity exercise session over 4 weeks.…”
Section: Hypoxic-hyperoxic Exposuresmentioning
confidence: 99%